2022
DOI: 10.3389/fmed.2022.1052921
|View full text |Cite
|
Sign up to set email alerts
|

Oncology and cardiology positron emission tomography/computed tomography faced with COVID-19: A review of available literature data

Abstract: The COVID-19 pandemic has forced people to significantly change their lifestyles and attitudes, and has greatly burdened healthcare delivery systems worldwide. The redistribution of the medical delivery system to maintain normal medical care while responding generously to COVID-19 is a continuing challenge that weighs heavily on medical institutions. Among imaging modalities, chest X-rays and computed tomography (CT) examinations have clearly made a large contribution to treatment of COVID-19. In contrast, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 212 publications
0
1
0
Order By: Relevance
“…F-FDG but also with other radiopharmaceuticals (1). For instance, Notohamiprodjo et al recently reported that the prevalence of vaccineassociated lymphadenopathy (VAL) on 18 F-rhPSMA-7.3 PET/CT was high, at 45% (2), but some points of the study deserve comment.…”
mentioning
confidence: 99%
“…F-FDG but also with other radiopharmaceuticals (1). For instance, Notohamiprodjo et al recently reported that the prevalence of vaccineassociated lymphadenopathy (VAL) on 18 F-rhPSMA-7.3 PET/CT was high, at 45% (2), but some points of the study deserve comment.…”
mentioning
confidence: 99%